Using Digital Storytelling to Improve Students’ Listening Ability - Nur Afana; Mashuri; Sriati Usman; Muhammad Arid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Listening ability is a skill that focuses on receiving, understanding and identifying a sound that includes several components of the language in this case specialized in English. Digital storytelling is the media that combine between audio and visual in story form. The purpose of this study is to prove whether or not there is an improvement in students' listening skills by using digital storytelling. This research used quasi-experimental. The population of this research was all of eight grade students at SMP Negeri 3 Banawa. The sample was 24 students from class D in experimental class and 24 students from class E in control class. After collecting data and conducting simple statistical analysis, it was found that the mean score of the experimental class (26.25) was higher than the control class (22.5). Then after applying a significant level of 0.5, it was found that the t-count (1.84) was higher than the t-table (1.68). It means the hypothesis is accepted. In conclusion, digital storytelling can improve the listening skills of the eighth grade students.